The Forest Schoolmaster - Rosegger, Peter, 1843-1918; Skinner, Frances E. (Salt Lake City, UT : Project Gutenberg, 2014)
"The Forest Schoolmaster" by Peter Rosegger is a fictional novel written in the late 19th century. The story revolves around the experiences of a new schoolmaster in a remote village in the Austrian Alps, where the narrative delves into the intricacies of rural life, the challenges he faces in educating the local children, and the diverse personalities of the villagers. The backdrop of the forest and the simplicity of village life serve as essential elements that shape the narrative. At the start of "The Forest Schoolmaster," the reader is introduced to the enchanting yet rugged natural surroundings of Winkelsteg, a small village enveloped by towering pines and rocky terrain. The protagonist arrives in this tranquil yet stark environment after a tumultuous journey, reflecting on the loneliness and transformation he feels. As he settles into the schoolhouse, he learns about the mysterious disappearance of the previous schoolmaster, gaining insights from the villagers who express their mixed feelings about him. The opening sets a contemplative tone as the new schoolmaster grapples with his purpose amidst the rustic charm and challenges of his new life, intertwining themes of introspection, duty, and community. (This is an automatically generated summary.)
Release date is 2014-10-22
Produced by Al Haines
Keywords: Teachers -- Fiction; Villages -- Fiction; Austrian fiction -- Translations into English